China's regional disparities: Experience and policy - Fan, Shenggen; Kanbur, Ravi; Zhang, Xiaobo (Elsevier, 2011)
This paper assesses the evolution of regional disparities in China, and brings information and trends up to date. Based on this assessment, it presents the broad outline of a strategy to harmonize growth and regional equity. We consider three elements of this strategy: infrastructure, social investment and protection, and governance reform. Specific policies within this broad strategy are then discussed in light of international experience. We also propose that the Chinese government take an experimental approach to interventions, as it did in the early period of agricultural reforms, learning lessons from the outcomes before scaling up.